2021
DOI: 10.1101/2021.02.01.21250493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex disparities and neutralizing antibody durability to SARS-CoV-2 infection in convalescent individuals

Abstract: The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome-related coronavirus-2 (SARS-CoV-2) has now caused over 2 million deaths worldwide and continues to expand. Currently, much is unknown about functionally neutralizing human antibody responses and durability to SARS-CoV-2. Using convalescent sera collected from 101 COVID-19 recovered individuals 21-212 days after symptom onset with forty-eight additional longitudinal samples, we measured functionality and durability of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Plasma samples were collected to evaluate immune response and serology using antigen-capture enzyme-linked immunosorbent assays. [17][18][19]…”
Section: Clinical and Immunologic Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma samples were collected to evaluate immune response and serology using antigen-capture enzyme-linked immunosorbent assays. [17][18][19]…”
Section: Clinical and Immunologic Outcomesmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 17 May 12];Available from: https://www.prnewswire.com/news-releases/phase-3-preventiontrial-showed-81-reduced-risk-of-symptomatic-sars-cov-2-infections-with-subcutaneousadministration-of-regen-cov-casirivimab-with-imdevimab-301266366.html All rights reserved. No reuse allowed without permission.…”
mentioning
confidence: 99%
“…Plasma samples were heat inactivated at 56°C for 30 minutes, then total Ig binding to the receptor binding domain (RBD) of the SARS-CoV-2 spike protein was measured using a previously described enzyme-linked immunosorbent (ELISA) assay [16,17]. Briefly, biotinylated recombinant antigen produced in mammalian cells consisting of SARS-2 Spike RBD is captured on a 96-well ELISA plate coated with streptavidin.…”
Section: Serologymentioning
confidence: 99%
“…The serum sample at 1:40 dilution is incubated with the RBD-captured wells, and bound antigen detected using HRP conjugated anti-goat total (IgG, IgM and IgA) antibody on a microplate reader. This in-house ELISA was previously evaluated on a large panel of well characterized samples and shown to have high sensitivity and specificity for detecting SARS-CoV-2 infection [16,17].…”
Section: Serologymentioning
confidence: 99%
“…Others have found no consistent IgG/IgA correlation for intensity of production [34]. Quantitation by most methods increase with the severity of infection [33,34,36,41,50,52,56,60,[70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87]. Severe disease may be associated with a delay of the humoral response [88].…”
Section: Immunogens and Humoral Immunitymentioning
confidence: 99%